Silazanes, a novel flax fibers functionalization: Effect on silicone-based composites. (March 2023) - Ishak, Antoine; Sonnier, Rodolphe; Otazaghine, Belkacem; Longuet, Claire
Graphical abstract: Abstract: The natural fibers use as reinforcement for composites is a topical subject. Usually, chemical functionalization is used in order to improve the compatibility between natural fibers and polymer matrices, for cross-linkable systems, the grafting agent used for fiber modification can also participate in the three-dimensional network formation and therefore improve the composite mechanical properties. In this study, a silazane: 1, 3-divinyltetramethyldisilazane (DVTS) was used for the first time as a flax fibers modification to introduce at their surface vinyl groups, via covalent bonds, that can react during the polysiloxane system cross-linking. The reaction conditions for the flax functionalization were investigated, especially the alkaline pre-treatment impact of the fibers before grafting and the nature of solvent used during the reaction. Scanning electron microscope (SEM) analyses shown a high interfacial adhesion functionalized fibers/matrix. Finally, tensile tests showed a significant increase of composites Young's modulus containing functionalized flax fibers.